2011
DOI: 10.1002/hed.21944
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of free flap volume changes in head and neck reconstruction

Abstract: Use of free flaps with a high ratio of fat to muscle is sustainable and can gain volume over time, as transplanted fat can increase depending on host condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 57 publications
(67 reference statements)
2
66
4
Order By: Relevance
“…In a previous report, Fujioka et al 2) , Siebert et al 10) and Siebert and Longaker 11) reported considerable change in amount of tissue with rectus RAMFs. In another report 15) , however, Yamaguchi et al reported that such change was absent in RAMFs and anterolateral thigh flaps. In the present study, only FFs and RAMFs were investigated.…”
Section: Discussionmentioning
confidence: 91%
“…In a previous report, Fujioka et al 2) , Siebert et al 10) and Siebert and Longaker 11) reported considerable change in amount of tissue with rectus RAMFs. In another report 15) , however, Yamaguchi et al reported that such change was absent in RAMFs and anterolateral thigh flaps. In the present study, only FFs and RAMFs were investigated.…”
Section: Discussionmentioning
confidence: 91%
“…Minor complications that did not require additional operation or reoperation in the early postoperative period were not influenced by radiation exposure in this study. Local abscesses due to postoperative discharge or hematoma and fistulae were managed by using normal techniques such as the transplantation of tissue with rich blood flow, appropriate flap configuration, and packing of dead space . Most patients in group A were cured through conservative treatment because approximately two thirds of the complications experienced by this group were minor.…”
Section: Discussionmentioning
confidence: 99%
“…Mourad et al reported that radiation therapy significantly increased the duration of heterotopic ossification. In addition, the soft tissues of the fistula do not tend to adhere together, and the localization of abscess is difficult to clarify, permitting infection to spread and necessitating additional surgery . Blood flow through tissues is decreased in the radiation field, and spontaneous healing is also delayed.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 The objective of this study was to reassess the relationship between previous treatments, anastomosed vessels, side of the neck where anastomosis was performed, and complications following multiple free flap reconstructions in the head and neck.…”
Section: Introductionmentioning
confidence: 99%